O itinerário filosófico do romance em György Lukács - Martins, Willian Mendes [UNIFESP] (2020)
The subject of this work is the form of the novel in some works of the Hungarian thinker György Lukács (1885-1971). We follow the evolution and the developments delineated by the thinker within some works, which according to our interest, are central. Thus, we aim to point to the possibilities established by the author for a concept of romance that is, or pretends to be, universalizing while not losing the uniqueness of each specific romanesque work.